PUBLICZNE PROTESTY ANTYABORCYJNE W ŚWIETLE ORZECZNICTWA SĄDÓW KANADYJSKICH - Maroń, Grzegorz (Zeszyty Prawnicze, 2016)
Public Pro-life Protests in Canadian Case Law Summary The article deals with the legal standards applied in public anti-abortion protests in Canada. On the basis of an examination of Canadian case law, the author argues that the restrictions on pro-life protests are disproportionate with respect to the objective of ensuring safe access to women’s reproductive rights. The Access to Abortion Services Act and court injunctions are preventing pro-lifers from demonstrating in the vicinity of abortion clinics in defence of the right to life of unborn children. The degree to which pro-lifers’ constitutional freedom of speech is being infringed is in breach of the principles of the liberal state. The right to express opposition to abortion is also limited, although to a lesser extent, in other public places, such as street pavements and squares, university campuses and airport terminals. In the author’s view, imprisonment as the penalty for peaceful protest against the Canadian abortion law – for example, Linda Gibbons spent a total of over 10 years in prison for her pro-life activities! – is inherently incompatible with the essence of a “free and democratic society” as defined in Article 1 of the Canadian Charter of Rights and Freedoms.